Inibidor de tripsina de Spodoptera frugiperda: extração de folhas de mamona, purificação, identificação e atividade biológica - Ramos, Vinicius de Oliveira (2016)
Acting in collaboration with the technological development, which increases crop productivity, are the studies on control of harmful organisms. Among all methods used, the traditional methods that employ agrochemicals to control its populations have been losing effect in the control of herbivore insects. This is due to, in great part, the indiscriminate and without adequate technical monitoring use. These factors, associated with the practice of monoculture, has selected populations of insects resistant to agricultural pesticides. The search for new control methods that do not physiologically affect populations of beneficial insects and present lower environmental impact is necessary in this context. In this work, we conducted an investigation of trypsin inhibitors that act reducing the absorption efficiency of amino acids by caterpillars of the species Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae). For this, chemometric optimization methods were developed for the extraction, purification, identification and structural characterization of the inhibitory molecule, and evaluation of how the insect is affected during its development, in addition of studying the from in which this compound acts, specifically, over the trypsin of the armyworm. The extraction of the inhibitor was optimized by means of chemometrics, un der conditions of 1 g of castor bean leaf meal (CBLM) in 48.6 mL of ethanol 71.7%, extracted by 60 min of ultrasonic bath at 40oC, with re-extraction in the same conditions, which produced extract with anti-trypsin activity of 94,837.14 mUTI g-1. The CBLM extract was purified in prep HPLC, and two compounds with apparent trypsin inhibition, identified as adenosine and ricinine. However, after purification, only ricinine inhibited trypsin in vitro, with 103.21 mUTI g-1. The extract was added to the diet offered to the caterpillars, resulting in a reduction of digestion, since all treatments presented higher concentration of proteins in the feces when compared to the control.